Rapid diagnosis of hot spot failure of crystalline silicon PV module based on I-V curve. (September 2019) - Ma, Mingyao; Liu, Heng; Zhang, Zhixiang; Yun, Ping; Liu, Fang
Abstract: Hot spot failure of PV modules has become one of the most important factors affecting the reliability of PV power generation systems. This study proposes a hot spot fault diagnosis method based on I-V curve of PV modules, which is based on distance calculation between scan points and lines formed by the points. By this method, various types of I-V curves can be quickly distinguished to diagnose hot spot faults. Finally, the diagnostic effect of the method was evaluated through a large number of PV power station field tests. Highlights: The types of hot spot modules were classified into three types based on the I-V curves. The mechanism of hot spot failure was studied and analyzed the causes of the characteristics of each types of I-V curves. This study proposes a new hot spot fault diagnosis method based on I-V curve of PV modules. The diagnostic effect of the proposed method were verified and analyzed the cause of the diagnosis error.